Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.envint.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ambient air pollution on global DNA methylation in healthy adults: A seasonal follow-up

Abstract: Decreased global DNA methylation in whole blood was associated with exposure to NO2, PM10, PM2.5 and O3 at the home addresses of non- adults. Most effects were observed for the 5- to 30-day moving average exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 52 publications
4
56
3
1
Order By: Relevance
“…We found higher global 5mC in males than females, consistent with previous studies conducted in Chinese populations and in a Belgian population; 26,35,36 findings were similar for global 5hmC. However, the ratio of 5mC/5hmC was higher in our data compared to previous studies.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…We found higher global 5mC in males than females, consistent with previous studies conducted in Chinese populations and in a Belgian population; 26,35,36 findings were similar for global 5hmC. However, the ratio of 5mC/5hmC was higher in our data compared to previous studies.…”
Section: Discussioncontrasting
confidence: 44%
“…Although, the 5mC (6.61%) levels differed between 7-fold and 21-fold across the 3 studies; the levels found in this study are more similar to those reported by De Prins et al (4.3%). 26 Previous investigations have suggested that DNA methylation is highly sensitive to environmental exposures, [7][8][9][10][11] including air pollution. To the best of our knowledge, the present study is the first human investigation of both 5hmC and 5mC in relation to PM exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, researchers are finding it worthwhile to investigate a link of PM 2.5 exposure with adverse birth outcomes, 21,22 epigenetic alteration, [23][24][25][26][27][28][29][30][31][32][33][34][35][36] infant mortality, [37][38][39][40][41][42] athero sclerosis, [43][44][45] stroke, 46-50 rheumatic autoimmune diseases, 51,52 central nervous system disorders, [53][54][55][56][57] and diabetes. [58][59][60] Since many of these health conditions are interlinked, comprehensive studies are required to better understand the impact of PM 2.5 .…”
Section: Neurotoxic Effectsmentioning
confidence: 99%
“…2,3 Exposure to environmental factors such as smoking, alcohol and air pollution are now known to cause both specific and widespread epigenetic alterations that affect gene expression. [4][5][6] There is also now a push to develop therapies that influence epigenetic changes including the histone deacetylase (HDAC) inhibitors such as givinostat. [7][8][9] This issue also includes outstanding updates of more traditional areas of study, including the effect of exposure to smoking and industrial chemicals and infectious agents.…”
mentioning
confidence: 99%